Multiprofessional Residency in Mental Health: Contributions to the training of critical subjects in the field of Psychosocial Care (Research, Society and Development, 2023)
The aim of this dissertation is to analyze the contributions of a Program of Multi-professional Residency in Mental Health for training individuals with critical thinking in the area of psychosocial care, taking a case study of the multi-professional residency in mental health of UNIVASF (Universidade Federal do Vale do São Francisco) as a starting point. The study involved a combination of structured interviews and supplementary documental analysis. The results showed that fundamental aspects of practices in psychosocial care were observed, aligned with the Brazilian Psychiatric Reformation, focusing on actions with a territorial and communal basis; the practical aspect of residency was highlighted to those in this course. There is an explicit emphasis in autonomy to undertake the residency, propositional to the exercise of co-responsibility of it, culminating in the creation of important initiatives of the interns in their practices; these professionals acknowledge the organizational support provided by the present manager in the autonomy, encouragement for innovation in their work, appreciation, aptitude for constant communication, participation in decision making and planning, and so on. Similarly, the rise of ingenious and transformative individuals, as critical professionals, was evidenced, emphasized by the proposition for modifications/changes in work organization, from the residency forward. Thus, the transformations performed by the program graduates in the work organization and at the clinic for psychosocial care were demonstrated, under the observation of the practitioners, indicating the existence of resourceful methods that have been breaking the structure of rigid and oppressive practices in mental health care.